Reliability of Positive and Negative Symptom Scale (PANSS) Indonesian Version in Acehnese Population - Juwita Saragih; Endang Mutiawati Rahayuningsih; Irwan Saputra; Marty Mawarpury (GLOBAL HEALTH SCIENCE GROUP, 2025)
The positive and negative syndrome scale (PANSS) has been widely used and validated for the assessment of severity of schizophrenia symptoms. However, the reliability of PANSS Indonesian version in Acehnese population has yet been divined. Research objective: to examine the reliability of PANSS in Acehnese schizophrenic patients. Methodology: A cross sectional study was conducted at Mental Hospital, Banda Aceh, Indonesia, from February to May 2024. Patients aged 18 and above, who were diagnosed with schizophrenia were included in this study, meanwhile patients with organic mental disorders, and history of alcohol or drug consumption were excluded. Two independent psychiatrists separately assessed the patients using PANSS, which consisted of 3 components: positive symptoms (P subscore - 7 questions), negative symptoms (N subscore – 7 questions) and general psychopathology symptoms (G score - 16 questions). Inter-rater reliability was measured using the intraclass correlation coefficient (ICC), in which ICC ≥ 0.60 was considered good. Results: Of twenty subjects enrolled, 70% were males, and the median age was 35 years (23-54). The overall ICC was excellent = 0.987 (0.982-0.994) on 95% confidence interval. Conclusion: PANSS is a reliable tool to assess the severity of schizophrenia in Acehnese population, emphasizing its importance in the clinical setting.